Selective Growth of Zn–Co–Se Nanostructures on Various Conductive Substrates for Asymmetric Flexible Hybrid Supercapacitor with Enhanced Performance. Issue 2 (20th December 2019) - Chebrolu, Venkata Thulasivarma; Balakrishnan, Balamuralitharan; Chinnadurai, Deviprasath; Kim, Hee‐Je
Abstract: Hybrid supercapacitors have received great interest in the field of electric vehicles and wearable electronic devices. However, developing new electrode material with high capacity and supporting substrates with good stability is still a big challenge. Herein, a facile electrodeposition technique is applied to grow Zn–Co–Se on various conductive substrates for hybrid supercapacitor. Among all, NF‐supported Zn–Co–Se electrode shows a high specific capacitance of 313.45 C g −1 and good cyclical stability of 95% retention over 3000 cycles. Interestingly, the assembled hybrid supercapacitor (Zn–Co–Se @Graphene–Ink) as the core and the outer electrode yield an ultrahigh energy density of ≈16.97 W h kg −1 at a power density of ≈539.63 W kg −1 with a maximum operating voltage of 1.6 V. Even at high power density of 13 499 W kg −1, the energy density can still retain 7.76 W h kg −1 with excellent cycling performance of 95% of capacity maintenance after 5000 cycles. For the real‐time applications, a series of two ASC devices could light up blue and green (LEDs) with high intensity and a multifunction sensor monitoring time with temperature and humidity is operated. Hence, the work presents a fresh route for designing metal selenides for energy storage and conversion applications. Abstract : A facile electrodeposition technique is applied to the growth of Zn–Co–Se on various conductive substrates and further the asymmetric hybrid supercapacitor (FAHSC) is employed as an energy source for various devices including green and red light‐emitting diodes (LEDs) and a multifunction electronic display, indicating its potential practical applications in hybrid electric vehicles and portable electronics.